Improving antibiotic prescribing in neonatal units: time to act. Issue 2 (30th October 2010) - Russell, Alison Bedford; Sharland, Mike; Heath, Paul T
Abstract : Antibiotics are increasingly prescribed in the peripartum period, for both maternal and fetal indications. Their effective use can be life-saving, however, injudicious use drives antibiotic resistance and contributes to the development of abnormal faecal flora and subsequent immune dysregulation. Neonatal units are a high risk area for the selection and transmission of multi-resistant organisms. Very few new antibiotics with activity against Gram-negative bacteria are under development, and no significantly new Gram-negative antibiotics will be available in the next decade. This review seeks to summarise current practice, and suggests restrictive antibiotic strategies based on epidemiological data from recently published UK neonatal infection surveillance studies.